Confidence in communicating with patients with cancer mediates the relationship between rehabilitation therapists' autistic-like traits and perceived difficulty in communication. Issue 2 (21st January 2018) - Hayashibara, Chinatsu; Inagaki, Masatoshi; Fujimori, Maiko; Higuchi, Yuji; Fujiwara, Masaki; Terada, Seishi; Okamura, Hitoshi; Uchitomi, Yosuke; Yamada, Norihito
Abstract: Objective: Recently, rehabilitation therapists have become involved in cancer rehabilitation; however, no communication skills training that increases the ability to provide emotional support for cancer patients has been developed for rehabilitation therapists. In addition, no study has examined associations between rehabilitation therapists' communication skills and their level of autistic-like traits (ALT), which are in-born characteristics including specific communication styles and difficulty communicating with patients. In this study, we aimed to investigate whether confidence in communicating with patients mitigates communication difficulties experienced by rehabilitation therapists who have high levels of ALT. Method: Rehabilitation therapists who treat patients with cancer completed self-administered postal questionnaires anonymously. Scores were obtained on the Autism-Spectrum Quotient short form, confidence in communication, and communication difficulties. We used covariance structure analyses to test hypothetical models, and confirmed that confidence in communication mediates the relationship between ALT and perceived communication difficulties. Results: Participants included 1, 343 respondents (49.6%). Autism-Spectrum Quotient scores were positively correlated with communication difficulties ( r = 0.16, p < 0.001). The correlation was mitigated by confidence in communication in the fit model. However, higher confidence in creating a supportive atmosphere was associated with more difficulty in communication ( r = 0.16, p < 0.001). Significance of results: Communication difficulty was linked to rehabilitation therapists' ALTs. By increasing confidence in areas of communication other than creation of a supportive atmosphere, ALT-related difficulties in communication may be ameliorated. Confidence to create supportive environments correlated positively with difficulty. Communication skills training to increase confidence in communication for rehabilitation therapists should be developed with vigilance regarding ALT levels.